2013
DOI: 10.3389/fnene.2013.00006
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic metabolic compartmentation during appetite regulation as revealed by magnetic resonance imaging and spectroscopy methods

Abstract: We review the role of neuroglial compartmentation and transcellular neurotransmitter cycling during hypothalamic appetite regulation as detected by Magnetic Resonance Imaging (MRI) and Spectroscopy (MRS) methods. We address first the neurochemical basis of neuroendocrine regulation in the hypothalamus and the orexigenic and anorexigenic feed-back loops that control appetite. Then we examine the main MRI and MRS strategies that have been used to investigate appetite regulation. Manganese-enhanced magnetic reson… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 108 publications
(138 reference statements)
0
19
0
1
Order By: Relevance
“…Increased intracellular potassium ions concentrations trigger an osmotically driven, aquaporin 4 (AQP4)-mediated, water transport culminating with astrocytic swelling (60). By using diffusion weighting imaging, Lizarbe et al have recently shown significant increases in the slow diffusion parameters, consistent with astrocyte swelling response, in the hypothalamus of fasted relative to satiated animals (61, 62). On these grounds, we may hypothesize that, whereas an initial leptin-driven glutamate uptake in astrocytes shows anorexigenic potential (by diverting glutamate from neurons and thereby reducing glutamatergic neurotransmission), an excessive glutamate uptake by astrocytes, as occurs under orexigenic fasting conditions, causes astrocyte’s swelling and eventual response by amino release to the synaptic cleft (63) (augmenting glutamatergic neurotransmission associated with appetite enhancement).…”
Section: Hypothalamic Glutamatergic Neurotransmissionmentioning
confidence: 83%
“…Increased intracellular potassium ions concentrations trigger an osmotically driven, aquaporin 4 (AQP4)-mediated, water transport culminating with astrocytic swelling (60). By using diffusion weighting imaging, Lizarbe et al have recently shown significant increases in the slow diffusion parameters, consistent with astrocyte swelling response, in the hypothalamus of fasted relative to satiated animals (61, 62). On these grounds, we may hypothesize that, whereas an initial leptin-driven glutamate uptake in astrocytes shows anorexigenic potential (by diverting glutamate from neurons and thereby reducing glutamatergic neurotransmission), an excessive glutamate uptake by astrocytes, as occurs under orexigenic fasting conditions, causes astrocyte’s swelling and eventual response by amino release to the synaptic cleft (63) (augmenting glutamatergic neurotransmission associated with appetite enhancement).…”
Section: Hypothalamic Glutamatergic Neurotransmissionmentioning
confidence: 83%
“…The central nervous system (CNS) plays an important role to balance the energy equation by regulating energy intake and expenditures, in the context of the homeostatic regulation of body weight [6]. Insulin and leptin are transported from the circulation into the brain [30]. Signaling of these hormones in the hypothalamus inhibits food intake and increases energy expenditure.…”
Section: Introductionmentioning
confidence: 99%
“…The low ADC values of hypothalamus and insula could be secondary to a dysfunction similar to hypothalamic and insular inflammation. A recent study that was conducted with fasting mice and humans using advanced diffusion also suggested that changes in diffusion parameters could be associated with hypothalamic inflammation (20).…”
Section: Discussionmentioning
confidence: 99%